Development and characterization of a technique for percutaneous radiologic gastrojejunostomy tube placement in the dog. Issue 5 (18th July 2016) - Mack, Rebekah M.; Staiger, Benjamin; Langlois, Daniel K.; Mehler, Stephen J.; Lam, Nathaniel; Moore, Trevor; Brown, Andrew; Beal, Matthew W.
Abstract: Objective: To develop and describe a technique for percutaneous radiologic gastrojejunostomy tube placement in the dog. Design: Prospective technique development study. Setting: University teaching hospital. Animals: Six healthy adult male Beagles. Interventions: Following anesthetic induction, fluoroscopic and ultrasound guidance were used to identify an appropriate gastropexy site on the left lateral abdomen. Gastropexy was performed using gastrointestinal suture anchors. An over‐the‐wire catheter technique using fluoroscopic guidance was used to achieve jejunal access. An 18F/8F, 58 cm, dual‐lumen gastrojejunal feeding tube was placed via serial over‐the‐wire dilation of the body wall using an 18F peel‐away introducer kit. Tube location was determined radiographically immediately following placement and on days 2, 4, after emesis on day 4, and at time of gastrojejunal feeding tube removal (day 16–18). Measurements and Main Results: Percutaneous radiologic gastrojejunostomy (PRGJ) tube placement was successful in all dogs. Median time to pyloric passage with the guide wire was 23.5 minutes (range, 9–93 minutes). Median total procedure time was 53 minutes (range, 49–113 minutes). Significant tube migration was not observed at any point during the study. One dog developed linear foreign body obstruction secondary to the tube on day 5 that was relieved by release of the jejunal component. Other complications were minor and included mild‐to‐moderate peristomal inflammation in all dogs and removal of the feeding tube on day 3 by 1 dog. Feedings were well tolerated in all dogs. Conclusions: PRGJ tube placement in the dog is a safe and minimally invasive technique that allows for jejunal feeding without surgery or endoscopy. The high success rates, acceptable procedural times, and minimal complications are appealing for use in critically ill patients. Although additional evaluations are needed, PRGJ tube placement may be considered for dogs that require postpyloric feeding with or without gastric decompression.